Development of the PRECIOUS Short-Form (PRECIOUS-SF) quality of care measure for children with serious illnesses - Felicia Jia Ler Ang; Yin Bun Cheung; Mihir Gandhi; Rahul Malhotra; Truls Ostbye; Chetna Malhotra; Cristelle Chu-Tian Chow; Poh Heng Chong; Zubair Amin; Teresa Shu Zhen Tan; Eric Finkelstein (Journal of Patient-Reported Outcomes)
Abstract Background Rising number of children with complex medical conditions necessitate regular healthcare quality evaluation to achieve optimal outcomes. To address the need for a periodic and quick assessment of quality of care in serious childhood illnesses, we developed a short version of previously validated 45-item PaRental Experience with care for Children with serIOUS illnesses (PRECIOUS) measure. Methodology PRECIOUS was administered by parents of children living with serious illnesses at two time-points (baseline and two weeks) in an online survey. PRECIOUS Short-Form (PRECIOUS-SF) items were derived from the full PRECIOUS measure, which comprises five scales, using an exploratory factor analysis and best subset regression. The measurement properties of PRECIOUS-SF scales were assessed using the concurrent validity using Pearson correlation (r) with the PRECIOUS scales, internal consistency (Cronbach’s α) within each scale, convergent validity with overall QoC rating, and test-retest reliability (intraclass correlation coefficient, ICC) between baseline and two-week responses. Results PRECIOUS-SF included 10 items across four scales – (1) access to financial and medical resources (2), collaborative and goal-concordant care (3), caregiver support and respectful care and (4) reduction of caregiving stressors. A fifth and optional scale was suggested for hospitalization-specific processes. PRECIOUS-SF scales correlated strongly with corresponding PRECIOUS scales (r = 0.91 to 0.98) and demonstrated satisfactory internal consistency (α = 0.77 to 0.91) and test-retest reliability (ICCs > 0.70). Conclusions PRECIOUS-SF demonstrated internal consistency, convergent validity, test-retest reliability, and concurrent validity with PRECIOUS. PRECIOUS-SF offers a practical tool for routine quality of care assessment in pediatric serious illnesses for promoting timely service evaluation and quality improvement.